EDITORIAL - Goh, Pauline Swee Choo; Ratnavadivel, Nagendralingan (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2018)
Welcome to Volume 4, Issue 1 of the Journal of Research, Policy & Practice of Teachers and Teacher Education (JRPPTTE). The journal, since its inception, has always been to further the study and critical discussion of all aspects regarding teaching and learning, and teacher education. The aim of the journal is to provide a platform for discussing the concerns, aspirations and innovation that occur in the everyday lives of teachers and teacher educators. This volume continues that tradition to allow teachers, teacher educators, postgraduate students and experienced researchers to review, to investigate, to examine, and to formalize areas of interest and importance in academia.